"Stink flirting" in ring‐tailed lemurs (Lemur catta): Male olfactory displays to females as honest, costly signals. Issue 12 (15th November 2017) - Walker‐Bolton, Amber D.; Parga, Joyce A.
Abstract : Sexual selection for honest behavioral displays of quality has driven the development of remarkably complex courtship behavior in many animal species. Olfactory displays are often overlooked as an area of inquiry compared to auditory and visual displays. Ring‐tailed lemur ( Lemur catta ) scent marking of substrates has been studied extensively, although the male olfactory displays of anointing and wafting tails to females has received relatively little attention. We studied the role of male olfactory displays to females, evaluating whether such signals function as honest, costly signals of male dominance status in two groups of wild L. catta at Berenty Reserve, Madagascar. Our results suggest that male tail anointing and tail wafting displays to pre‐estrous and estrous females are correlated with male dominance rank, and moreover appear to operate as costly signals, as such displays increase aggression received from males and females while other types of scent marking do not. Furthermore, females showed greater mating preference (as measured by sexual presents) for resident males who performed the "anoint tail" and "waft tail" displays towards them. When males perform the "anoint tail" and "waft tail" displays to females, they receive higher levels of aggression than if they were to perform other types of scent marking. Interestingly, immigrating (peripheral) males performed the "anoint tail" and "waft tail" displays at higher rates than resident males, which could honestly indicate their quality or may simply be associated with the alternative mating strategy of transferring between groups to gain mating opportunities. Our finding that tail anointing and tail wafting displays function as honest signals of dominance for resident males—and that these costly displays appear to positively affect female mate choice—is the first evidence of this function for this particular olfactory signal in L. catta . Abstract : Male tail anointing and wafting displays to pre‐estrous and estrous females are correlated with male dominance rank and appear to operate as costly signals. Females showed greater mating preference for resident males who performed the "anoint tail" and "waft tail" displays towards them.